PENCEGAHAN PENYAKIT INFEKSI MENULAR MELALUI UPAYA SANITASI DAN HIGIENE PERSONAL UNTUK PENCEGAHAN STUNTING DI DESA TABLOLONG KECAMATAN KUPANG BARAT KABUPATEN KUPANG NTT: PREVENTION OF INFECTIOUS DISEASES THROUGH PERSONAL SANITATION AND HYGIENE EFFORTS TO PREVENT STUNTING IN TABLOLONG VILLAGE, WEST KUPANG DISTRICT, KUPANG DISTRICT, NTT - Soleman Landi; Tadeus Andreas Lada Regaletha; Muntasir Muntasir (Pergizi Pangan DPD NTT, 2023)
Stunting is a chronic deficiency in nutritional status during a child's growth and development period determined from the Z-Score value of body length for age (PB/U) or height for age (TB/U) <-2 SD. Environmental health from the aspect of poor sanitation and hygiene will trigger digestive disorders which impact nutrition for growth and turn into the body's resistance to infection, thereby risking stunting in toddlers. Implementation of community service is designed in the form of planning service activities, creating health promotion information media, preparing supporting materials and arranging field activities, implementing service activities, and evaluating activities. The results of the service show the level of success that was carried out well and successfully. There is an increase in the level of knowledge of respondents regarding the prevention of infectious diseases through personal hygiene sanitation efforts. This can be seen from the results of the pre and post-test evaluations carried out where the average score of respondents' pre-test results was 87 which increased to 100 when the post-test was carried out. It is recommended that this service model can be implemented for different targets and locations. It is recommended that health workers provide outreach with practical and effective educational methods related to sanitation and hygiene so that the public can understand the importance of maintaining a healthy environment to avoid the occurrence of infectious diseases that have an impact on stunting.